Hierarchical nanoflowers assembled from MoS2/polyaniline sandwiched nanosheets for high-performance supercapacitors. (20th July 2017) - Chao, Jie; Deng, Junwen; Zhou, Weijia; Liu, Jiangwen; Hu, Renzong; Yang, Lichun; Zhu, Min; Schmidt, Oliver G.
Graphical abstract: Highlights: Hierarchical nanoflowers are assembled from MoS2 /PANI sandwiched nanosheets. The sandwiched structure enables efficient interface contact between MoS2 and PANI. The (002) interlayer spacing of MoS2 is expanded due to the intercalation of PANI. The MoS2 /PANI nanocomposite exhibit high capacitance and long cycle life. Abstract: To realize high capacitance and long cycle performance of supercapacitors, hierarchical microflowers assembled from MoS2 /polyaniline sandwiched nanosheets (MoS2 /PANI SNSs) have been developed as electrode materials. In the hybrid nanosheets, PANI intercalates into the (002) interlayer of MoS2, leading to enhanced electron transfer as well as expanded interlayers which is beneficial for ion diffusion kinetics. Furthermore, the hierarchical microflower-like structure prevents aggregation of MoS2 nanosheets, while the sandwich structure relieves the volume expansion and dissolution of PANI during repeated charge/discharge cycles. In the three-electrode test system for supercapacitors, the MoS2 /PANI SNSs Exhibit 245.5 F g −1 at a 10 A g −1 in the first cycle, and retain 212.6 F g −1 after 16000 cycles. Assembled as symmetric supercapacitors in the two-electrode configuration, the MoS2 /PANI SNSs show 81.3 F g −1 at 1 A g −1 in the first cycle, and retain 70.0 F g −1 after 8000 cycles.